2013
DOI: 10.1016/j.cosust.2012.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Establishing the links between economic development and the restoration of natural capital

Abstract: This article appeared in a journal published by Elsevier. The attached copy is furnished to the author for internal non-commercial research and education use, including for instruction at the authors institution and sharing with colleagues.Other uses, including reproduction and distribution, or selling or licensing copies, or posting to personal, institutional or third party websites are prohibited.In most cases authors are permitted to post their version of the article (e.g. in Word or Tex form) to their pers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
32
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 22 publications
2
32
0
Order By: Relevance
“…To fully evaluate the outcomes, all relevant variables, including the social ones, should be included. Barthélémy and Armani (2015) noted that social processes and local experiences are often ignored in restoration projects and Aronson et al (2010) and Blignaut et al (2013Blignaut et al ( , 2014 found that the benefits of restoration for society were not given due attention. In most of our case studies, however, the social component was fairly well included in the projects.…”
Section: Discussionmentioning
confidence: 99%
“…To fully evaluate the outcomes, all relevant variables, including the social ones, should be included. Barthélémy and Armani (2015) noted that social processes and local experiences are often ignored in restoration projects and Aronson et al (2010) and Blignaut et al (2013Blignaut et al ( , 2014 found that the benefits of restoration for society were not given due attention. In most of our case studies, however, the social component was fairly well included in the projects.…”
Section: Discussionmentioning
confidence: 99%
“…Research on restoration has mainly focused on terrestrial, rather than on marine coastal ecosystems (Blignaut et al. ) and the monetary value of the ecosystem services (de Groot et al. ).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the cost for coastal restoration projects depends on the ecosystem type, national economic strength, restoration project framework and engineering technique carried out (Blignaut et al. , Bayraktarov et al. ).…”
Section: Introductionmentioning
confidence: 99%